Accuracy of Acceleration Time of Distal Arteries to Diagnose Severe Peripheral Arterial Disease - Trihan, Jean-Eudes; Mahé, Guillaume; Croquette, Magali; Coutant, Vicky; Thollot, Cécile; Guillaumat, Jérôme; Lanéelle, Damien (Frontiers in Cardiovascular Medicine, 2022)
Context Ankle-brachial index (ABI) and toe-brachial index (TBI) are the recommended tests for the diagnosis of lower extremity peripheral artery disease (PAD) and the assessment of its severity, whereas Doppler ultrasound (DUS) is usually used to localize vascular lesions. However, the performance of DUS as an alternative to TBI and ABI measurement is unknown. Objective The goals were (i) to evaluate the correlation between DUS parameters of distal arteries of the lower extremities with TBI in patients with PAD; (ii) to evaluate the correlation between DUS parameters of distal arteries with ABI; and (iii) to assess the diagnostic accuracy of maximal acceleration time of pedal arteries to detect toe pressure ≤30 mmHg. Methods An observational retrospective study was conducted for 1 year on patients with the diagnosis of PAD on DUS. Demographic data, ABI, TBI, and DUS parameters of the dorsal pedis and lateral plantar arteries (DPA and LPA) were recorded. Results Seventy-seven patients with 88 limbs were included, aged 69 [interquartile range: 11 years] with 28.6% of diabetic patients. The highest acceleration time of either DPA or LPA (ATmax) was the most correlated to TBI on both univariate (r = −0.78, p < 0.0001) and multivariate analysis (p < 0.0001). DUS parameters had a weaker correlation with ABI. ATmax > 215 ms showed high diagnosis accuracy to a toe pressure of 30 mmHg or less [sensitivity of 86% [0.57–0.98] and negative predictive value of 97% [0.89–1.00]]. Conclusion ATmax demonstrates a high correlation with TBI in patients with PAD, and high diagnostic accuracy for detection of critical limb ischemia. Based on these results, ATmax can represent the next step in evaluating PAD severity with DUS, in patients with advanced lower extremity PAD.